PENGETAHUAN MAHASISWA KEBIDANAN TENTANG IMUNISASI PENTAVALEN - Darah Ifalahma; Afrinnindya Niken Fachruniza (OVUM : Journal of Midwifery and Health Sciences, 2021)
Pentavalent immunization is a combination of DPT, Hb and HiB immunizations.Based on a preliminary study using the interview method conducted on 10midwifery student respondents, the results showed that 4 people knew about themeaning of pentavalent immunization, 3 people knew the meaning and benefits ofpentavalent immunization and 3 people only knew about the schedule for givingpentavalent immunization. This study aims to determine the knowledge ofmidwifery students about pentavalent immunization.The type of research used is descriptive. The instrument used is a questionnaire.The sampling technique uses Probability Sampling, namely Total Sampling. Theresearch sample was all second-level students totaling 75 respondents. Theanalysis used univariate with frequency distribution.Based on data analysis from 75 respondents, the majority had sufficientknowledge about pentavalent immunization, namely 53 people (70.7%), 10 peoplehad good knowledge (13.3%), and 12 people had less knowledge (16%). The conclusion of this study is the level of knowledge of midwifery students levelII about pentavalent immunization, the majority of respondents have a sufficientlevel of knowledge.